COPING WITH DROUGHT AMONG PASTORAL AND AGRO-PASTORAL COMMUNITIES IN EASTERN ETHIOPIA - Kassa Belay (University of Goettingen, 2006)
This paper examines coping strategies of pastoral and agro- pastoral communities in six districts of Eastern Ethiopia. Data collected from a random sample of 360 households were used in the study. The results of the study indicate that the study area has been stricken by recurrent droughts since the early 1980s and that drought has increasingly devastating effects on the lives of pastoral and agro-pastoral communities. In response to the degrading production environment, the pastoral and agro- pastoral communities become more provident and employ a variety of techniques to cushion themselves against contingencies. Moreover, the results of the study show that most of the coping strategies are aimed at counteracting the detrimental effects of droughts after their occurrence rather than identifying the root causes of droughts. Finally, we suggest the need for political actors to move from crisis management through emergency intervention to improving the capability to cope in changing environmental conditions.
Keywords: coping strategies; diversification; drought; migration; Livestock raiding; coping strategies; diversification; drought; migration; Livestock raiding